Non-Communicable Disease Education through Risk Factor Screening on Employees of Bondowoso Campus, University of Jember - Arina Mufida Ersanti; Lirista Dyah Ayu Oktafiani (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
Non-Communicable Disease is a chronic disease that tends to last a long time and can cause death. It can cause individuals to become less productive. However, controlling risk factors through early detection can prevent these problems. At this time, early detection is mostly carried out at the village / health facilities level, not yet at work / institutional level. Bondowoso Campus Jember University is one of the largest educational institutions in the BASUKI RAYA area, which has many employees, and an average age of over 20 years, which is the productive age group. Early detection through Non-Communicable Disease screening activities is important in preventing and reducing morbidity and mortality due to the disease. This activity is also useful in regularly monitoring the health of employees and also minimizing lost opportunities for employees to carry out early detection of diseases due to examinations. Methods of this activity include counseling, early detection of PTM as well as counseling and counseling based on screening results. Data analysis were performed using univariate and bivariate. Different test was performed using Wilcoxon with a level of ɑ = 0.05. The results showed that there was an increase in employee knowledge regarding non-communicable diseases and how to prevent them. (p = 0.03, sig <0.05).